Plant Phenotypic Traits Eventually Shape Its Microbiota: A Common Garden Test - Li, Yunshi; Wu, Xiukun; Chen, Tuo; Wang, Wanfu; Liu, Guangxiu; Zhang, Wei; Li, Shiweng; Wang, Minghao; Zhao, Changming; Zhou, Huaizhe; Zhang, Gaosen (Frontiers in Microbiology, 2018)
Plant genotype drives the development of plant phenotypes and the assembly of plant microbiota, but the potential influence of the plant phenotypic characters on its microbiota is not well characterized and the co-occurrence interrelations for specific microbial taxa and plant phenotypic characters are poorly understood. We established a common garden experiment, quantifying prokaryotic and fungal communities in the phyllosphere and rhizosphere of six spruce (Picea spp.) tree species, through Illumina amplicon sequencing. We tested for relationships between bacterial/archaeal and fungal communities and the phenotypic characters of their plant hosts. Host phenotypic characters including leaf length, leaf water content, leaf water storage capacity, leaf dry mass per area, leaf nitrogen, phosphorous, and potassium contents, leaf δ13C values, stomatal conductance, net photosynthetic rate, intercellular carbon dioxide concentration, and transpiration rate were significantly correlated with the diversity and composition of the bacterial/archaeal and fungal communities. These correlations between plant microbiota and suites of host plant phenotypic characters suggest that plant genotype shape its microbiota by driving the development of plant phenotypes. This will advance our understanding of plant-microbe associations and the drivers of variation in plant and ecosystem function.